2016
DOI: 10.1186/s13075-016-1079-x
|View full text |Cite
|
Sign up to set email alerts
|

Association between Staphylococcus aureus nasal carriage and disease phenotype in patients affected by systemic lupus erythematosus

Abstract: Background: Staphylococcus aureus (SA) is a commensal bacterium representing one of the most important components of the skin microbiome, mostly isolated in the anterior nares. A higher rate of SA nasal colonization in patients affected by Wegener's granulomatosis and rheumatoid arthritis compared with healthy subjects (HS) has been described. No studies focusing on systemic lupus erythematosus (SLE) are available. We aimed at analyzing the prevalence of SA nasal carriers in an SLE cohort and evaluating correl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 34 publications
(44 reference statements)
0
14
1
1
Order By: Relevance
“…Although more than 30% of healthy individuals are colonized asymptomatically by S. aureus 75,76 , it can cause a wide spectrum of infections: some are limited to a single hair follicle (furuncle), others involve subcutaneous tissues (cellulitis), and the most serious feature potentially fatal penetration into any organ in the body, including bone (osteomyelitis), bloodstream (bacterial sepsis), and heart valves (bacterial endocarditis). S. aureus has also been implicated in the pathogenesis of chronic diseases such as atopic dermatitis 22,7779 , and more recently in systemic lupus erythematosus with renal and skin involvement 80 .…”
Section: Host–pathogen Interactionsmentioning
confidence: 99%
“…Although more than 30% of healthy individuals are colonized asymptomatically by S. aureus 75,76 , it can cause a wide spectrum of infections: some are limited to a single hair follicle (furuncle), others involve subcutaneous tissues (cellulitis), and the most serious feature potentially fatal penetration into any organ in the body, including bone (osteomyelitis), bloodstream (bacterial sepsis), and heart valves (bacterial endocarditis). S. aureus has also been implicated in the pathogenesis of chronic diseases such as atopic dermatitis 22,7779 , and more recently in systemic lupus erythematosus with renal and skin involvement 80 .…”
Section: Host–pathogen Interactionsmentioning
confidence: 99%
“…It has been suggested that the microbial persistence is a factor contributing to chronicity in inflammatory arthritides [38]. In particular, P. gingivalis DNA seems to be able to induce the production of proinflammatory cytokines such as interleukin (IL)-6, IL-1 and tumour necrosis factor (TNF), playing a central role in RA pathogenesis [39][40][41]. This production seems to occur through the signalling pathway of Toll-like receptor (TLR)-9, expressed highly in pathological periodontal tissue in comparison with healthy tissue [39,42,43].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, disruption of the epithelial barrier, which is important in promotion of S. aureus colonization (Wanke et al, 2013), is able to drive lupus disease activity (Clark et al, 2015). Moreover, S. aureus is the leading cause of bacteremia in patients with lupus, and its carriage may be associated with disease flares and development of lupus nephritis (Chen et al, 2008;Conti et al, 2016;Hajialilo et al, 2015). Reflecting the importance of S. aureusedriven immune activation, repeated injections of S. aureus superantigen in wild type mice results in the development of a disease that mimics lupus (Chowdhary et al, 2012).…”
Section: Introductionmentioning
confidence: 99%